Restless legs syndrome/Willis-Ekbom disease in multiple sclerosis: a contributing factor for anxiety, disability, sleep disorder, and quality of life - Seferoğlu, Meral; Sivaci, Ali Özhan; Tunç, Abdulkadir (Arquivos de Neuro-Psiquiatria, 2020)
Background: Restless legs syndrome (RLS) is one of the most common and burdensome sleep disorders in the course of multiple sclerosis (MS). Objective: To evaluate common MS-related symptoms and consequences between groups with and without RLS and further assess the association of quality of life determinants with RLS symptom severity. Methods: According to their RLS status, 46 relapsing-remitting MS patients were divided into MS-RLS+ (n=19) and MS-RLS- groups (n=27). Specific questionnaires were administered to assess the patients’ health-related quality of life (HRQoL), fatigue levels, sleep quality, daily sleepiness, anxiety, and depression symptoms. Functional capacity was examined using the Expanded Disability Status Scale (EDSS). Results: The prevalence of RLS was 41.3%. Compared to the MS-RLS- group, those with RLS had higher EDSS scores, more cranial and spinal lesions, longer disease duration, and were older. In the MS-RLS+ group, symptom severity scores were positively correlated with higher anxiety and poorer sleep quality. The symptom severity score was negatively correlated with mental HRQoL and pain scores. Conclusion: In conclusion, the findings of the current study indicate the negative impact of RLS on functional capacity, anxiety, sleep quality, and mental HRQoL of MS patients. Further studies using more accurate diagnostic strategies for identifying RLS and other sleep disorders are necessary to clarify the association of MS with RLS and explore relevant clinical implications.
Keywords: Restless Legs Syndrome; Sleep Disorder; Multiple Sclerosis